The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.4049/jimmunol.169.5.2461
|View full text |Cite
|
Sign up to set email alerts
|

The Subpopulation of CD4+CD25+ Splenocytes That Delays Adoptive Transfer of Diabetes Expresses L-Selectin and High Levels of CCR7

Abstract: Recently, CD4+CD25+ T cells have been implicated in the control of diabetes, suggesting that the inflamed islets of Langerhans in prediabetic NOD mice are under peripheral immune surveillance. Here we show that CD4+CD25+ splenocytes inhibit diabetes in cotransfer with islet-infiltrating cells. Furthermore, CD62L expression is necessary for this disease-delaying effect of CD4+CD25+ cells in vivo, but not for their suppressor function in vitro. We demonstrate that the CD4+CD25+CD62L+ splenocytes express CCR7 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
273
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(293 citation statements)
references
References 35 publications
(30 reference statements)
15
273
0
3
Order By: Relevance
“…CD62L + and CD62L -populations are similar in that they are both suppressive, although the CD62L + population is a more efficient suppressor population than the CD62L -population [48]. Prior studies by Alyanakian et al [49] reported a central role of CD4 + CD62L + T cells in controlling autoimmune disease in the NOD mouse.…”
Section: Discussionmentioning
confidence: 95%
“…CD62L + and CD62L -populations are similar in that they are both suppressive, although the CD62L + population is a more efficient suppressor population than the CD62L -population [48]. Prior studies by Alyanakian et al [49] reported a central role of CD4 + CD62L + T cells in controlling autoimmune disease in the NOD mouse.…”
Section: Discussionmentioning
confidence: 95%
“…The selective/specific removal of activated T cells expressing surface PD-1 without direct manipulation of Treg minimizes the possibility of altering Treg function. This could represent a potential advantage of PD-1 over CD62L to allow the selection of purer populations of Treg (34,35). In fact, the latter procedure would require the positive selection of CD4 ϩ CD25 ϩ CD62L ϩ by means of specific mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…CD25 + CD4 + Treg play a central role in the maintenance of immunological homeostasis and self-tolerance [29]. Treg are by no means homogeneous, but rather can be subdivided into naïve-like subsets, which preferentially recirculate through lymphoid tissues, and effector/memory subsets, which efficiently migrate into peripheral sites and sites of ongoing immune responses [30][31][32][33]. Thus, it is not surprising that Treg display a high HR versatility [31,[34][35][36][37][38][39].…”
mentioning
confidence: 99%